Reliability Analysis of Bearing Capacity of Soil of Combined Pile Raft Foundation (CPRF) of Historic Dharahara - Lamsal, Laxman; Acharya, Indra Prasad (Kathford Journal of Engineering and Management, 2023)
When the raft foundation alone does not fulfil the design requirement, it may be possible to enhance the performance of the raft by economical addition of piles to transfer the heavy load to soft soil with a rather low total or differential settlement called a combined pile raft foundation (CPRF). The proposed twenty-one storey Dharahara tower at Sundhara, Kathmandu is being constructed with CPRF.This paper focuses on the reliability index, the probability of failure and reliability of Dharahara. Statistical analysis is carried out to determine the mean and variance of log-normally distributed geotechnical uncertainty parameters cohesion, unit weight, friction angle and the normally distributed loading on the foundation. First, the limit equilibrium performance function equation of bearing capacity is prepared using a First Order Reliability Method (FORM) and then solving the value of reliability index by coding on C Programming Language. Obtained value is validated with Euro Code-Basis of Structural Design. The results show that the reliability of the designed foundation system of Dharahara is 0.99999872% and the probability of failure is 0.00000128%. Sensitivity analysis is performed by varying uncertainty parameters and the result shows that friction angle is more sensitive than the other three parameters.